Enhancing Coherent Optical Communication Performance Using FBG as Dispersion Compensator - Alalfi, Raghad Mohammad Fayez; Alsalem, Abdulkareem (Journal of engineering sciences and information technology, 2023)
This study focuses on improving the performance of a coherent optical communication system using 16-QAM modulation with a data rate of 10 Gb/s, when increasing the transmission distance by compensating chromatic dispersion affecting the propagated signal in single-mode optical fibres, using dispersion compensators. A dispersion compensation model consists of a linear chirped apodized fibre Bragg grating CFBG followed by an identical four stages cascaded of a Uniform fibre Bragg Gratings UFBGs. This comparative study includes cases based on Grating length for CFBG at a fixed value of the effective refractive index to determine the appropriate grating length. Results using Optisystem.19 showed an improvement in system performance, in addition to the possibility of increasing the optical fibre length up to 180 km, with the BER under 10-3.
Keywords: coherent optical communication system; chromatic dispersion; fiber Bragg grating; Optisystem